Effects of Weekly Iron and Folic Acid Supplements on Malaria Risk in Nulliparous Women in Burkina Faso: A Periconceptional, Double-Blind, Randomized Controlled Noninferiority Trial. (4th May 2018) - Gies, Sabine; Diallo, Salou; Roberts, Stephen A; Kazienga, Adama; Powney, Matthew; Brabin, Loretta; Ouedraogo, Sayouba; Swinkels, Dorine W; Geurts-Moespot, Anneke J; Claeys, Yves; D'Alessandro, Umberto; Tinto, Halidou; et al.
Abstract : Weekly iron supplementation, given to young nulliparous women living in a malaria-endemic area, neither improved iron status nor increased malaria risk, suggesting that current iron recommendations may need revisiting for these women. Abstract: Background: The safety of iron supplementation for young women is uncertain in malaria-endemic settings. Methods: This was a double-blind, randomized controlled noninferiority trial in rural Burkina Faso. Results: A total of 1959 nulliparae were assigned to weekly supplementation (60 mg iron and 2.8 mg folic acid) (n = 980) or 2.8 mg folic acid (n = 979) until first antenatal visit (ANC1), or 18 months if remaining nonpregnant. Three hundred fifteen women attended ANC1, and 916 remained nonpregnant. There was no difference at ANC1 in parasitemia prevalence (iron, 53.4% [95% confidence interval CI, 45.7%–61.0%]; control, 55.3% [95% CI, 47.3%–62.9%]; prevalence ratio, 0.97 [95% CI, .79–1.18]; P = .82), anemia (adjusted effect, 0.96 [95% CI, .83–1.10]; P = .52), iron deficiency (adjusted risk ratio [aRR], 0.84 [95% CI, .46–1.54]; P = .58), or plasma iron biomarkers. Outcomes in nonpregnant women were parasitemia (iron, 42.9% [95% CI, 38.3%–47.5%]; control, 39.2% [95% CI, 34.9%–43.7%]; prevalence ratio, 1.09 [95% CI, .93–1.28]; P = .282); anemia (aRR, 0.90 [95% CI, .78–1.05]; P = .17), and iron deficiency (aRR, 0.99 [95% CI, .77–1.28]; P = .96), with no iron biomarker differences. Conclusions: Weekly iron supplementation did not increase malaria risk, improve iron status, or reduce anemia in young, mostly adolescent menstruating women, nor in early pregnancy. World Health Organization Guidelines for universal supplementation for young nulliparous women may need reassessment. Clinical Trials Registration: NCT01210040.